Applied neuropsychology of attention : theory, diagnosis, and rehabilitation - Leclercq, Michel, 1946-; Zimmermann, Peter, 1936- (Psychology Press, 2002)
This collection of essays forms a comprehensive overview of this crucial component of human cognitive function.